Population Ecology of Vermitechnologically Suitable Earthworm, Perionyx sansibaricus (Michaelsen) in Ranchi, Jharkhand, India - Mandal, Samir Kumar; Srivastava, Rohit; Kachhap, Sheelu; Baxla, Neha Swati; Shalini; Subarna, Sweta; Sinha, Manoranjan Prasad (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The paper discusses the rate of reproduction, population growth, and density of the earthworm, Perionyx sansibaricus. The key findings are as follows: 1. Perionyx sansibaricus exhibited bimodality in its reproductive strategy, with two peaks observed in December 2021 and July 2022, recording values of 1.06 and 1.28, respectively. 2. The rate of population growth peaked at +3.202 in July 2022, when environmental resistance was at its lowest, and reached a minimum of -0.875 in June 2022. 3. Population density was highest at 9045/m² in August 2022 and lowest at 345/m² in June 2022, with juvenile proportions ranging from 8.33% to 27.70%, immature proportions from 44.50% to 100%, and mature proportions from 16.21% to 31.89%. 4. The biomass of Perionyx sansibaricus peaked at 2111.18 g live weight/m² in August 2022 and dropped to a minimum of 60.38 g live weight/m² in June 2022. High density and rapid reproduction rates confirm that Perionyx sansibaricus is an efficient agent of vermitechnology.